SHPB Testing and Analysis of Bedded Shale under Active Confining Pressure - Guoliang Yang; Jingjiu Bi; Xuguang Li; Jie Liu; Yanjie Feng (Journal of Engineering)
Shale gas is the most important new energy source in the field of energy, and its exploitation is very important. The research on the dynamic mechanical properties of shale is the premise of exploitation. To study the dynamic mechanical properties of shale from the Changning-Weiyuan area of Sichuan Province, China, under confining pressure, we used a split Hopkinson pressure bar (SHPB) test system with an active containment device to carry out dynamic compression tests on shale with different bedding angles. (1) With active confining pressure, the shale experiences a high strain rate, and its stress-strain curve exhibits obvious plastic deformation. (2) For the same impact pressure, the peak stress of shale describes a U-shaped curve with an increasing bedding angle; besides, the peak stress of shale with different bedding angles increases linearly with rising confining pressure. The strain rate shows a significant confining pressure enhancement effect. With active confining pressure, the peak strain gradually decreases as the bedding angle increases. (3) As a result of the influence of different bedding angles, the dynamic elastic modulus of shale has obvious anisotropic characteristics. Shale with different bedding angles exhibits different rates of increase in the dynamic elastic modulus with rising confining pressure, which may be related to differences in the development of planes of weakness in the shale. The results of this study improve our understanding of the behavior of bedded shale under stress.